2022
DOI: 10.2147/jmdh.s368832
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and Its Associated Factors Among Helicobacter pylori-Infected Patients Attending at University of Gondar Comprehensive Specialized Hospital, Gondar, North-West Ethiopia: A Comparative Cross-Sectional Study

Abstract: Background Dyslipidemia refers to a lipid profile disturbance due to decreased high-density lipoprotein cholesterol and elevated low-density lipoprotein cholesterol, triglycerides, and total cholesterol. Helicobacter pylori infection can lead to some appetite-related disorders that may cause deregulated absorption of nutrients in the digestive system, contributing to changes in serum lipids. The purpose of this study is to assess dyslipidemia and its associated factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Similarly, the TC and HDL levels were downregulated in patients with HP infection ( Tali et al, 2022 ). Nigatie et al (2022) demonstrated that the prevalence of dyslipidemia in patients with HP infection was as high as 71.8%. The median TG, TC, and LDL levels in patients with HP infection (93, 143, and 108 mg/dL, respectively) were significantly higher than those in patients without HP infection (83, 125, and 95 mg/dL, respectively) ( Nigatie et al, 2022 ).…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the TC and HDL levels were downregulated in patients with HP infection ( Tali et al, 2022 ). Nigatie et al (2022) demonstrated that the prevalence of dyslipidemia in patients with HP infection was as high as 71.8%. The median TG, TC, and LDL levels in patients with HP infection (93, 143, and 108 mg/dL, respectively) were significantly higher than those in patients without HP infection (83, 125, and 95 mg/dL, respectively) ( Nigatie et al, 2022 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“… Nigatie et al (2022) demonstrated that the prevalence of dyslipidemia in patients with HP infection was as high as 71.8%. The median TG, TC, and LDL levels in patients with HP infection (93, 143, and 108 mg/dL, respectively) were significantly higher than those in patients without HP infection (83, 125, and 95 mg/dL, respectively) ( Nigatie et al, 2022 ). Previous studies have demonstrated that HP infection was positively correlated with TC, TG, and LDL levels and negatively correlated with HDL levels ( Shimamoto et al, 2020 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…Lipid profile abnormalities may be influenced by H. pylori infection, as evidenced by numerous epidemiological reports on eradication therapy. 62,63 A meta-analysis of 24 studies, including 4 randomized controlled trials (RCTs) and 20 non-RCTs, with a total of 5270 subjects, revealed that post-eradication lipid levels showed an increase in high-density lipoprotein cholesterol (HDL-C; mean difference (MD) = 2.28 mg/dL, 95% CI: 1.90-2.66) and triglycerides (TG; MD = 3.22 mg/dL, 95% CI: 1.13-5.31) compared to pre-eradication levels. 63 However, no difference was observed in LDL-C levels (MD = −2.33 mg/dL, 95% CI: −4.92 to 0.26).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Dyslipidemia was characterized when the total cholesterol level was >5.17 mmol/L and/or the triglyceride level was >1.69 mmol/L and/or the LDL-C level was >2.59 mmol/L and/or the HDL-C level was <1 mmol/L in males and/or the HDL-C level was <1.3 mmol/L in females [23,35].…”
Section: Operational/case Definitionmentioning
confidence: 99%
“…Plasma lipid and lipoprotein abnormality constitute dyslipidemia and are metabolically interrelated [22]. The H. pyloritriggered inflammatory response alters the nutrient absorption and serum lipid profile [23]. The intestinal absorption of these factors is crucial to maintain their optimum level in the body [24].…”
Section: Introductionmentioning
confidence: 99%